2018
DOI: 10.3390/en11071657
|View full text |Cite
|
Sign up to set email alerts
|

Optimization Strategy for Economic Power Dispatch Utilizing Retired EV Batteries as Flexible Loads

Abstract: With the increasing penetration of new and renewable energy, incorporating variable adjustable power elements on the demand side is of particular interest. The utilization of batteries as flexible loads is a hot research topic. Lithium-ion batteries are key components in electric vehicles (EVs) in terms of capital cost, mass and size. They are retired after around 5 years of service, but still retain up to 80% of their nominal capacity. Disposal of waste batteries will become a significant issue for the automo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Typically, an EV lithium-ion (Li-ion) battery pack needs to be replaced when its capacity reduces to 80% of its rated capacity due to the safety and performance considerations 3 . The expensive disposal process and low recycling rate (less than 2%) cause environmental concerns e.g., active metals resource depletion 4,5 . Reuse of retired EV batteries for stationary applications e.g., in distributed energy systems (DES), has been suggested as a promising way to catalyse a resource-circular battery industry and create new supply chains for energy storage 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Typically, an EV lithium-ion (Li-ion) battery pack needs to be replaced when its capacity reduces to 80% of its rated capacity due to the safety and performance considerations 3 . The expensive disposal process and low recycling rate (less than 2%) cause environmental concerns e.g., active metals resource depletion 4,5 . Reuse of retired EV batteries for stationary applications e.g., in distributed energy systems (DES), has been suggested as a promising way to catalyse a resource-circular battery industry and create new supply chains for energy storage 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…In respect of the issues above, there are many studies on the power dispatch strategy with high proportion of renewable energy [11][12][13][14][15][16]. The coordination among multi-sources in the power system that is utilized to improve the consumption of renewable power energy is one of the most important strategies.…”
Section: Introductionmentioning
confidence: 99%
“…are flexible sources to promote their development and utilization [11,12]. On the load side, the flexible loads such as electric vehicles [13] and energy storage [14] are introduced to increase the system flexibility, which can improve the reserve capability and promote the consumption of renewable energy. The pumped storage is a kind of large, flexible, and fast response capability owning energy storage unit [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies carried out on the management on "New Energy" vehicles refueling stations have confirmed the active impact on economical operation and network reinforcement deferral [4,5]. In order to reduce the operational cost of the integrated smart EV's charging station with battery energy storage, Yan et al [6] proposed a four-stage optimization and control algorithm.…”
Section: Introductionmentioning
confidence: 99%